Apakah Instagram lebih penting dibandingkan Inovasi Produk Dan Citra Merek Terhadap Minat Beli Produk Kuliner? Studi Kasus: Kaum Milenial di daerah Jakarta Selatan - Fachrul Husain Habibie; Amalia Mustika; Deivy Zulyanti Nasution; Willy Arafah; Nurbaeti Nurbaeti (At-Tadbir : jurnal ilmiah manajemen, 2022)
In the current era of globalization and the Covig 19 pandemic, it is not only product innovation and brand image that need attention, but how a product is known by the public, especially millennials, thereby increasing their buying interest. This research was conducted to analyze the highest influence of Instagram, Product Innovation and Brand Image on Purchase Intention. The location chosen in this research is South Jakarta. The method used is descriptive correlation which explains the effect of all variables on buying interest. The results of this study indicate that the influence of Instagram is greater than product innovation and brand image of culinary products for millennials during the current Covid 19 pandemic in South Jakarta. It is hoped that the results of this research can be useful for culinary SMEs and other small culinary actors.